2001
DOI: 10.1007/s11661-001-0118-6
|View full text |Cite
|
Sign up to set email alerts
|

Discontinuous precipitation at [001] twist boundaries in Cu-0.75 wt pct Be alloy bicrystals

Abstract: The misorientation dependence of discontinuous precipitation (DP) at [001] twist boundaries in Cu-0.75 wt pct Be alloy bicrystals has been systematically investigated in the temperature range 523 to 723 K. A good correlation is found between both the incubation period, , to initiate DP and cell growth rate, v, and the energy of boundaries. The maximum of and the minimum of v occur where the cusps of the boundary energy exist. The formation and growth of DP are easier at higher-energy boundaries. The DP cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 15 publications
2
3
0
Order By: Relevance
“…11 revealed that, for the two models, the larger the Q b value, the larger is the (s D b ) 0 value. This result is in accordance with that of the previous studies [2,3].…”
Section: Growth Kineticssupporting
confidence: 94%
See 4 more Smart Citations
“…11 revealed that, for the two models, the larger the Q b value, the larger is the (s D b ) 0 value. This result is in accordance with that of the previous studies [2,3].…”
Section: Growth Kineticssupporting
confidence: 94%
“…However, the cell growth rate of DP was unchanged and linear in spite of the formation of ", ' or . This is in agreement with the result of our previous work [2,3]. That is, the DP cells at the [001] symmetric tilt boundaries nucleate more rapidly than those at the [011] tilt boundaries.…”
Section: Variation In Cell Formation and Growth With The Misorientsupporting
confidence: 93%
See 3 more Smart Citations